Sebični gen, psihologija in psihoanaliza - Pečjak, Vid (Psihološka obzorja (Ljubljana), 1995)
According to the theory of selfish gene the unity of life is not a person, but a gene, which replicates and passes over to descendents. Therefore the main human functions are multiplication, which is dependent on sex, and survival, which is dependent on satisfaction of psychological needs, which remind us of Freudian libido and eros, whereas the influence of the destructive genes of tanatos. The functions are not necessary conscious. Sinceidentical genes defend each other, genetically similar people support themselves whereas genetically different people compete for the sources. Many psychological and social behaviors are congruent with the theory of selfish gene, even the Oedipal conflict, but many not, for example some forms of altruism, homosexuality and celibate.
Keywords: geni; dednost; sebičnost; psihologija; psychology; psihoanaliza